A method for real-time measurement of the pH on the surface of the anode catalyst of a membrane electrode in a proton exchange membrane water electrolyzer under working conditions
Patent Information
- Application Number
- CN202611289312.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-23
AI Technical Summary
[0007]本发明的目的是解决现有技术中质子交换膜水电解阳极催化剂表面微环境认识不足、工况不可知、高温强酸环境下测量难的技术问题,并提供一种可实时测量质子交换膜水电解槽工况时膜电极阳极催化剂表面pH的方法
1、本发明采用碳酸钠掩埋高温煅烧、酸洗除杂、长期纯水浸泡除微量残留杂质的工艺制备铱/氧化铱传感探针,工艺简单易操作,无高污染试剂,绿色环保;所得氧化铱传感层电位响应贴合能斯特规律,电极可逆性、检测重复性优异,长期测试电位漂移小,可在PEM电解槽高温、强酸性、高氧化电位复杂工况下持续稳定采集电位信号。
Smart Images

Figure CN122962075A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical analysis technology, specifically relating to a method for real-time measurement of the pH on the surface of the anode catalyst of a proton exchange membrane water electrolyzer under operating conditions. Background Technology
[0002] Proton exchange membrane electrolysis (PEMWE) has dynamic advantages such as compact system, fast response, high current density, and the ability to directly obtain high-purity hydrogen. Compared with traditional hydrogen production methods that rely on fossil fuels (such as natural gas steam reforming and coal gasification), the core advantage of PEMWE is that its feedstock is water, which is widely available and does not consume limited resources. When coupled with clean power sources such as wind, solar or nuclear power, it can achieve true "green hydrogen" production with extremely low carbon emissions over its life cycle. Although the current cost is high, with technological progress and the decline in the cost of clean energy, it is considered to be the hydrogen production route with the greatest potential for sustainable development in the future (Ji, M., & Wang, J. (2021). Review and comparison of various hydrogen production methods based on costs and life cycle impact assessment indicators. International Journal of Hydrogen Energy, 46(77), 38612-38635.).
[0003] Compared to traditional alkaline water electrolysis (AWE) and high-temperature solid oxide electrolysis (SOEC), the core advantage of proton exchange membrane water electrolysis (PEMWE) lies in its dynamic response capability (second-level start-up and shutdown, wide load range) that perfectly matches the volatility of renewable energy sources such as wind and solar power, while also possessing higher current density (1-2 A cm⁻¹). 2Higher hydrogen purity and a more compact system design. Although proton exchange membrane water electrolyzers currently rely on precious metal catalysts such as iridium and ruthenium, resulting in higher costs, compared to the low current density and poor flexibility of traditional alkaline water electrolysis and the high-temperature material degradation and sealing problems of high-temperature solid oxide electrolysis, proton exchange membrane water electrolysis is considered to be the most suitable hydrogen production technology for coupling intermittent renewable energy sources (Buttler, A., & Spliethoff, H. (2018). Current status of water electrolysis for energy storage, grid balancing and sector coupling via power-to-gas and power-to-liquids: A review. Renewable and Sustainable Energy Reviews, 82, 2440-2454.).
[0004] The insufficient stability of anode catalysts in proton exchange membrane water electrolyzers under acidic and high oxidation potential conditions is a core challenge to their commercialization. Taking the currently irreplaceable iridium-based catalyst as an example, its scarcity and high cost severely restrict the large-scale promotion of the technology. Ruthenium-based catalysts, which are cheaper, suffer from even worse stability due to the rapid loss of active components caused by the formation of soluble RuO4. Highly active catalysts that perform excellently in ideal three-electrode tests often experience a sharp drop in stability of several orders of magnitude in the solid electrolyte membrane electrode environment of a real proton exchange membrane water electrolyzer. Because the catalytic reaction in the membrane electrode occurs at the solid-solid interface between the ionomer and the catalyst particles, the proton concentration is dynamically changing, and conventional methods cannot accurately determine this key parameter (Zhou, Y., Guo, W., Xing, L., Dong, Z., Yang, Y., Du, L., Xie, X., & Ye, S. (2024). Keys to Unravel the Stability / Durability Issues of Platinum-Group-Metal Catalysts toward Oxygen Evolution Reaction for AcidicWater Splitting. ACS Central Science, 10(11), 2006-2015.). Therefore, directly measuring the actual pH value of the catalyst surface is a prerequisite for understanding the catalyst failure mechanism under operating conditions.
[0005] During the start-up, shutdown, or power fluctuations of a proton exchange membrane water electrolyzer, changes in local current and mass transfer can cause drastic pH fluctuations at the catalyst / membrane interface. These fluctuations are a significant trigger for catalyst corrosion and the decline in ionomer flowability (Zhu, Y., Guo, F., Zhang, S., Wang, Z., Chen, R., He, G., Sun, X., & Cheng, N. (2025). Stimulating Efficiency for Proton Exchange Membrane Water Splitting Electrolyzers: From Material Design to Electrode Engineering. Electrochemical Energy Reviews, 8(1), 33.). By monitoring pH changes at the active sites of the catalyst in situ in real time, the dynamic structure-potential-pH relationship can be precisely established. This can fundamentally guide the design of highly durable catalysts that can stably exist in real strongly acidic microenvironments, or optimize operating strategies to mitigate acid corrosion.
[0006] Iridium oxide electrodes possess the core performance characteristics of high sensitivity and rapid response, with their potential response typically approaching or exceeding the Nernst theoretical slope (-59.2 mV / pH). Simultaneously, their extremely short response time allows them to capture rapid pH dynamics. Regarding long-term stability, performance-optimized iridium oxide electrodes can operate stably continuously for days to months in complex environments with extremely low drift. However, current applications of iridium oxide electrodes for measuring catalyst surface pH are mainly in metal corrosion and protection science, and marine environmental and water monitoring. Their application in proton exchange membrane water electrolysis anode catalysts remains limited to three-electrode testing. Therefore, developing a method for real-time measurement of the pH on the membrane electrode anode surface during proton exchange membrane water electrolyzer operation is imperative. Summary of the Invention
[0007] The purpose of this invention is to solve the technical problems of insufficient understanding of the microenvironment on the surface of the anode catalyst in proton exchange membrane water electrolysis, unknown operating conditions, and difficulty in measurement under high temperature and strong acid conditions in the prior art, and to provide a method for real-time measurement of the pH on the surface of the anode catalyst of the membrane electrode under the operating conditions of a proton exchange membrane water electrolyzer.
[0008] The present invention addresses the above-mentioned technical problems by adopting the following technical solution.
[0009] This invention provides a method for real-time measurement of the pH on the surface of the anode catalyst of a proton exchange membrane electrolyzer under operating conditions. The method involves: preparing an iridium / iridium oxide sensing probe with pH-responsive characteristics; in-situ implanting the sensing probe into the anode catalyst micro-region of the proton exchange membrane electrolyzer; constructing an in-situ self-consistent electrochemical testing system in the cell using an in-situ reversible hydrogen electrode; obtaining the probe potential-pH response relationship through electrochemical calibration; and combining this with synchronous acquisition technology of electrolysis conditions and electrochemical signals to achieve in-situ, real-time detection of the dynamic pH of the anode catalyst micro-region under actual energized operating conditions of the proton exchange membrane electrolyzer. Specifically, the method includes the following steps: Step 1: Prepare the iridium / iridium oxide sensing probe for testing: 11. At room temperature, polish iridium wire with a diameter of 0.1-0.2 mm, a length of 10-15 cm, and a purity of 99.99% using 2000-3000 grit sandpaper; place the polished iridium wire in a 1:1 mixture of ethanol and water for ultrasonic cleaning for 1-5 hours, and then dry it in an oven at 50-70℃ for 5-10 hours.
[0010] 12. Spread a layer of finely ground anhydrous sodium carbonate powder at the bottom of the corundum crucible, then place the iridium wire in the crucible and continue to completely cover the iridium wire with anhydrous sodium carbonate powder.
[0011] 13. Place the corundum crucible in a muffle furnace and heat it to 800-900℃ at a heating rate of 2-10℃ / min. Hold the temperature for 1-5 h to form a uniform, dense iridium oxide sensing functional layer with stable pH electrochemical response characteristics on the surface of the iridium wire in situ. Allow it to cool naturally to room temperature. Rinse the iridium wire alternately with 0.1-0.5 M hydrochloric acid solution and deionized water to completely dissolve and remove the surface sodium carbonate solid. Then dry it in an oven at 100-150℃ for 9-15 h.
[0012] 14. Soak the dried iridium wire in deionized water for 10-15 days, changing the deionized water every 3 days to obtain an iridium / iridium oxide sensing probe with an iridium oxide coating on the surface. By soaking in pure water for a long time, the trace sodium carbonate impurities remaining in the micropores of the iridium oxide film after high-temperature calcination and acid washing are fully washed away, avoiding the interference of alkaline residues on the pH detection baseline and test accuracy, and obtaining a clean and impurity-free sensing probe.
[0013] 15. One end of the iridium / iridium oxide sensing probe is wrapped with copper foil as a conductive lead-out end. Two layers of 8 µm thick perforated Nafion film are used to completely wrap the sensing area of the probe to ensure that the probe can contact the gas and to avoid short circuits during the operation of the electrolytic cell. The Nafion film is pre-perforated to ensure that hydrogen and oxygen can normally contact the electrode surface.
[0014] 16. Before testing, immerse the prepared iridium / iridium oxide sensing probe in deionized water for 10-15 hours for later use.
[0015] Step 2, Calibration of probe potential-pH linearity: A three-electrode calibration system was constructed, using an iridium / iridium oxide sensing probe as the working electrode, a calomel electrode as the reference electrode, and a carbon rod as the counter electrode. The open-circuit potential E was measured in a standard buffer solution with a pH range of 2-7. OCP A linear relationship between open circuit potential and pH value was established.
[0016] Step 3: Assembly of the proton exchange membrane water electrolyzer and in-situ electrode layout: One end of the platinum wire wrapped with copper foil is used as the conductive lead-out end, and the sensing area of the platinum wire is completely wrapped with two layers of perforated Nafion film with a thickness of 6-10 µm to form an in-situ reversible hydrogen electrode.
[0017] A proton exchange membrane with a double-sided catalyst layer constitutes the core component of the membrane electrode assembly (MEA). One side of the membrane is the anode catalyst layer, and the other side is the cathode catalyst layer. An electrolyzer is assembled by stacking layers. On the anode side, platinum-plated titanium felt and an anode pad are arranged sequentially from the anode catalyst layer outwards. On the cathode side, carbon paper and a cathode pad are arranged sequentially from the cathode catalyst layer outwards. During the assembly and stacking process, a detection electrode is simultaneously embedded. An iridium / iridium oxide sensing probe is placed between the anode catalyst layer and the titanium felt, and an in-situ reversible hydrogen electrode is placed between the cathode catalyst layer and the carbon paper, near the hydrogen outlet, ensuring the platinum wire is in a hydrogen-saturated environment. The thickness of the platinum-plated titanium felt is 400-420 µm, the anode PTFE pad is 400-420 µm, the carbon paper is 360-380 µm, and the cathode PTFE pad is 300-320 µm.
[0018] Step 4: Electrode placement and test system connection: Connect the blue electric test equipment to the electrolytic cell; the working electrode clamp of the Chenhua three-electrode test system holds the copper foil area of the anode iridium / iridium oxide sensing probe, while the reference electrode and counter electrode clamp hold the conductive area of the cathode platinum wire.
[0019] Step 5: In-situ pH test: Simultaneously activate the Blue Electricity testing system and the Chenhua three-electrode testing system, and acquire the open-circuit potential E measured by the Chenhua three-electrode system in real time. OCP By combining the pre-calibrated potential-pH linear relationship, real-time measurement of the pH on the anode catalyst surface under water electrolysis cell operating conditions can be achieved.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention uses a process of high-temperature calcination with sodium carbonate burial, acid washing to remove impurities, and long-term immersion in pure water to remove trace residual impurities to prepare iridium / iridium oxide sensing probes. The process is simple and easy to operate, without highly polluting reagents, and is green and environmentally friendly. The potential response of the obtained iridium oxide sensing layer conforms to the Nernst law, with excellent electrode reversibility and detection repeatability. The potential drift is small during long-term testing, and the potential signal can be continuously and stably acquired under the complex conditions of high temperature, strong acidity, and high oxidation potential in PEM electrolytic cells.
[0021] 2. In this invention, a micro iridium / iridium oxide sensing probe is sandwiched between the anode catalyst and the titanium felt, and a platinum wire coated with a Nafion membrane is configured as the cathode. This platinum wire serves as both the electrolysis counter electrode and the in-situ reversible hydrogen reference electrode, eliminating the need for an external reference electrode. The assembly process does not damage the original stacked structure of the membrane electrode and does not interfere with the electrolysis gas generation, proton conduction, and mass transfer processes. It can directly capture the real microenvironment signal of the catalytic interface during operation.
[0022] 3. This invention uses electrolysis control equipment and electrochemical signal acquisition equipment for synchronous testing, which can simulate real industrial conditions such as electrolytic cell start-up and shutdown, load variation, and wide current density fluctuation. Compared with traditional three-electrode offline detection, the measured pH dynamic change completely restores the step fluctuation law of the catalyst interface acidity and alkalinity under actual electrolysis conditions, and the data accuracy is greatly improved.
[0023] 4. This invention enables in-situ real-time quantitative detection of pH in micro-regions on the surface of the anode catalyst layer under energized conditions in a PEM water electrolyzer. It can intuitively obtain the dynamic evolution law of interface pH during variable load, establish the dynamic structure-activity relationship of microstructure-working potential-interface pH, and effectively solve the technical bottleneck of existing technologies that make it difficult to know the local microenvironment acidity and alkalinity of the anode catalyst under electrolysis conditions and the difficulty of in-situ detection of high temperature strong acid.
[0024] 5. Based on the real-time pH detection data of this invention, the failure mechanisms of corrosion dissolution and ionomer decay of precious metal anode catalysts such as iridium-based and ruthenium-based catalysts can be accurately analyzed. This provides measured data support for the development of high-stability, low-precious-metal oxygen evolution catalysts, the improvement of electrolyzer electrode structures, and the optimization of variable power operation control schemes. It is conducive to improving low-cost, high-performance PEM hydrogen production equipment and lays a solid scientific foundation for the large-scale production of green hydrogen. Attached Figure Description
[0025] Figure 1 This is a schematic diagram of the iridium / iridium oxide sensing probe prepared in an embodiment of the present invention; Figure 2 This is a schematic diagram of the assembly of the proton exchange membrane water electrolyzer and the in-situ electrode arrangement in an embodiment of the present invention; Figure 3 A scanning electron microscope (SEM) image of the iridium / iridium oxide sensing probe prepared in Example 1 of the present invention; Figure 4The layered image of the energy dispersive X-ray spectrum (EDS) of the iridium / iridium oxide sensing probe prepared in Example 1 of the present invention; Figure 5 The total number of EDS layered images of the iridium / iridium oxide sensing probe prepared in Example 1 of the present invention are shown. Figure 6 The open-circuit potential E of the iridium / iridium oxide sensing probe prepared in Example 1 of this invention. OCP Calibration plots showing the linear relationship between the solution and different pH solutions (2-7); Figure 7 The graph shows the stability test results of the iridium / iridium oxide sensing probe prepared in Example 1 of this invention in different pH solutions (2-7); Figure 8 The diagram shows the repeatability test results of the iridium / iridium oxide sensing probe prepared in Example 1 of this invention in different pH solutions (2-7); Figure 9 The diagram shows the reversibility test of the iridium / iridium oxide sensing probe prepared in Example 1 of this invention in different pH solutions (2-7) in the neutral-to-acid and acid-to-neutral directions. Figure 10 The response rate test graph of the iridium / iridium oxide sensing probe prepared for Example 1 of the present invention was obtained by rapidly decreasing the pH from 7 to 2 and repeating the test for three cycles. Figure 11 The testing of the iridium / iridium oxide sensing probe prepared in Example 1 of this invention in a three-electrode system is converted into the open-circuit potential E of a two-electrode system composed of iridium / iridium oxide and platinum wire in a proton exchange membrane water electrolyzer. OCP Linear relationship between the pH of the solution and the pH of the solution (2-7); Figure 12 The graph shows the relationship between pH and current density on the surface of the membrane electrode anode catalyst when iridium oxide is selected as the anode catalyst in the proton exchange membrane water electrolyzer assembled in Example 1 of the present invention.
[0026] Figure 13 The graph shows the relationship between pH and current density on the surface of the anode catalyst of the membrane electrode when ruthenium oxide is selected as the anode catalyst in the proton exchange membrane water electrolyzer assembled in Example 1 of the present invention. Detailed Implementation
[0027] To further understand the present invention, preferred embodiments of the present invention are described below in conjunction with specific embodiments. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention and not for limiting the claims of the present invention.
[0028] The raw materials used in the following examples are all analytical grade, commercially available conventional chemicals, and do not require further processing.
[0029] Example 1 This embodiment provides a method for real-time measurement of the pH on the surface of the anode catalyst of a proton exchange membrane water electrolyzer under operating conditions. The specific steps are as follows: Step 1: Prepare the iridium / iridium oxide sensing probe for testing: At room temperature, an iridium wire with a diameter of 0.1 mm, a length of 10 cm, and a purity of 99.99% was polished with 2500-grit sandpaper. The polished iridium wire was ultrasonically cleaned for 1 h in a 1:1 mixture of ethanol and water, followed by drying in a 50°C oven for 5 h. Anhydrous sodium carbonate was ground into fine powder using a mortar and pestle. A layer of anhydrous sodium carbonate was placed at the bottom of an alumina crucible, and the iridium wire was then placed inside and completely covered with anhydrous sodium carbonate. The alumina crucible was placed in a muffle furnace and heated to 850°C at a heating rate of 5°C / min, held for 5 h, and then allowed to cool naturally to room temperature. The iridium wire was rinsed alternately with 0.5 M hydrochloric acid solution and deionized water to completely dissolve and remove the surface sodium carbonate solids, followed by drying in a 120°C oven for 9 h. The dried iridium wire electrode was then immersed in a centrifuge tube filled with deionized water for 15 days to hydrate, with the deionized water being replaced every 3 days, resulting in an iridium / iridium oxide sensing probe with an iridium oxide coating on its surface. One end of the prepared iridium / iridium oxide sensing probe was wrapped with copper foil, and the sensing area of the probe was completely wrapped with two 8µm thick perforated Nafion films. The structure is as follows. Figure 1 As shown. Before testing, the prepared iridium / iridium oxide sensing probe was soaked in deionized water for 10 hours for later use.
[0030] Step 2, Calibration of probe potential-pH linearity: A three-electrode calibration system was constructed, using an iridium / iridium oxide sensing probe as the working electrode, a calomel electrode as the reference electrode, and a carbon rod as the counter electrode. The open-circuit potential E was measured in a standard buffer solution with a pH range of 2-7. OCP A linear relationship between open circuit potential and pH value was established.
[0031] Step 3: Assembly of the proton exchange membrane water electrolyzer and in-situ electrode layout: One end of a platinum wire wrapped in copper foil is used as the conductive lead-out end. Two layers of 6-10 µm thick perforated Nafion film completely encapsulate the sensing area of the platinum wire, forming an in-situ reversible hydrogen electrode. Its structure is as follows: Figure 1 As shown.
[0032] A Nafion 115 proton exchange membrane with a double-sided catalyst layer constitutes the core component of the membrane electrode assembly. One side of the membrane is the anode catalyst layer (iridium oxide or ruthenium oxide in this embodiment), and the other side is the cathode catalyst layer (Pt / C in this embodiment). An electrolyzer is assembled by stacking layers. On the anode side, from the anode catalyst layer of the membrane body outwards, a 410 µm thick platinum-plated titanium felt and a 400 µm thick anode PTFE pad are arranged sequentially. On the cathode side, from the cathode catalyst layer of the membrane body outwards, a 370 µm thick carbon paper and a 300 µm thick cathode PTFE pad are arranged sequentially. During the assembly and stacking process, a detection electrode is simultaneously embedded. An iridium / iridium oxide sensing probe is placed between the anode catalyst layer surface and the titanium felt, and an in-situ reversible hydrogen electrode is placed between the cathode catalyst layer and the carbon paper, near the hydrogen outlet, ensuring the platinum wire is in a hydrogen-saturated environment. The specific assembly structure is as follows: Figure 2 As shown.
[0033] Step 4: Electrode placement and test system connection: Connect the blue electric test equipment to the electrolytic cell; the working electrode clamp of the Chenhua three-electrode test system holds the copper foil area of the anode iridium / iridium oxide sensing probe, while the reference electrode and counter electrode clamp hold the conductive area of the cathode platinum wire.
[0034] Step 5: In-situ pH test: Simultaneously activate the Blue Electricity testing system and the Chenhua three-electrode testing system. The Blue Electricity testing system is set to a current density range of 0-2 A cm⁻¹. -2 Real-time acquisition of the open-circuit potential E measured by the Chenhua three-electrode system OCP By combining the pre-calibrated potential-pH linear relationship, real-time measurement of the pH on the anode catalyst surface under water electrolysis cell operating conditions can be achieved.
[0035] The surface morphology of the iridium / iridium oxide sensing probe of Example 1 was characterized, and the results are as follows: Figure 3 As shown in the scanning electron microscope (SEM) image, the iridium oxide film in the obtained iridium / iridium oxide sensing probe achieves uniform, continuous and dense coating on the surface of the iridium wire substrate. The iridium oxide film completely covers the length of the iridium wire without any exposed areas or large-area gaps. The film layer is composed of tightly packed nanoparticles with uniform thickness, and is tightly bonded to the iridium wire with no peeling at the edges.
[0036] Surface elemental content analysis was performed on the iridium / iridium oxide sensing probe of Example 1, and the results are as follows: Figure 4 Energy dispersive X-ray spectra (EDS) and Figure 5The total distribution spectrum shows that the carbon signal (26.31%) comes from the conductive adhesive. The content of each element after deducting the carbon signal is shown in Table 1. The iridium content is 82.78% and the oxygen content is 17.07%. The Ir / O mass ratio is close to the theoretical stoichiometric ratio, confirming that the main component of the iridium / iridium oxide electrode surface film is IrO2 oxide.
[0037] Table 1 Distribution Map Total Spectrum
[0038] The linear correlation between open-circuit potential and pH value established in step 2 of Example 1 is as follows: Figure 6 As shown, the electrode's pH sensitivity is -61.2 mV / pH, close to the theoretical response value of -59.2 mV / pH, confirming that the iridium / iridium oxide sensing probe has excellent pH responsiveness.
[0039] In a three-electrode system, the stability of the iridium / iridium oxide sensing probe from Example 1 was tested in solutions with different pH values (2-7), and the results are as follows: Figure 7 As shown, during the 120 s test, the open-circuit potential remained essentially unchanged, ΔE ocp <2 mV confirms the excellent stability of the iridium / iridium oxide sensing probe.
[0040] In a three-electrode system, the iridium / iridium oxide sensing probe of Example 1 was repeatedly tested in solutions with different pH values (2-7), and the results are as follows: Figure 8 As shown, the open-circuit potentials Eocp of the two tests were basically the same, confirming that the iridium / iridium oxide electrode has excellent repeatability.
[0041] In a three-electrode system, the potential of the iridium / iridium oxide sensing probe from Example 1 was measured in solutions with different pH values, both in the neutral-to-acid and acid-to-neutral directions. The results are as follows: Figure 9 As shown, the pH sensitivity in both cases (neutral → acidic and acid → neutral) is approximately 61 mV / pH, with a correlation coefficient exceeding 0.997. The standard deviation of potential change at each pH level is less than 10 mV, confirming the excellent pH detection reversibility of the iridium / iridium oxide sensing probe.
[0042] In a three-electrode system, the iridium / iridium oxide sensing probe of Example 1 was subjected to potential response measurements by rapidly changing the pH value from 7 to 2 (and vice versa). Three consecutive measurement cycles were performed, and the results are as follows: Figure 10 As shown, the potential response time of the iridium / iridium oxide sensing probe is less than 1 s, and the potential change after cycling is less than 5 mV, which confirms that the iridium / iridium oxide sensing probe has excellent response speed and stability under pH step changes.
[0043] For the iridium / iridium oxide sensing probe of Example 1, the three-electrode calibration system was transformed into a two-electrode system consisting of iridium / iridium oxide and platinum wire in a proton exchange membrane water electrolyzer. The results are as follows: Figure 11 As shown. The continuous hydrogen production at the cathode keeps the platinum wire in a hydrogen-saturated state, which can be considered equivalent to a reversible hydrogen reference electrode. The potential conversion formula is: E vs.RHE =E vs.SCE +E SCEvs.SHE +0.0591×pH, where the potential E of the saturated calomel electrode relative to the standard hydrogen electrode. SCE vs.SHE The value is taken as 288 mV, and the pH is set to 4 based on the pH of the Nafion 115 membrane surface where the platinum wire is located. Substituting these values into the calculation, the potential-pH correlation equation is obtained: Eoc = -0.0612 × pH + 1.19, which translates to pH = -16.3Eoc + 19.4. When the electrolyzer is running under load, only the open-circuit potential Eoc of the anode probe needs to be collected, and the real-time pH of the micro-region on the anode catalyst surface can be calculated by substituting it into this equation.
[0044] In the proton exchange membrane water electrolyzer assembled in Example 1, when iridium oxide was selected as the anode catalyst, the pH change on the surface of the anode catalyst of the membrane electrode with current density was as follows: Figure 12 As shown, the surface of iridium oxide gradually becomes more acidic as the current density increases, and the curve trend gradually decreases at higher current densities, which verifies the reason why iridium oxide has good stability at high current densities, that is, it has the ability to maintain a low level of surface acidity.
[0045] In the proton exchange membrane water electrolyzer assembled in Example 1, when ruthenium oxide was selected as the anode catalyst, the pH change of the anode catalyst surface of the membrane electrode with current density was as follows: Figure 13 As shown, the surface of ruthenium oxide gradually becomes more acidic as the current density increases. However, at higher current densities, the curve shows a gradually increasing trend, which verifies the reason why ruthenium oxide has poor stability at high current densities, namely, that the surface acidity increases significantly with increasing current density.
[0046] Obviously, the above embodiments are merely examples for illustrative purposes, and other variations or modifications can be made based on the above description. Therefore, obvious variations or modifications derived therefrom still fall within the protection scope of this invention.
Claims
1. A method for real-time measurement of the pH on the surface of the anode catalyst of a proton exchange membrane water electrolyzer under operating conditions, characterized in that, An iridium / iridium oxide sensing probe with pH-responsive characteristics was prepared and in-situ implanted into the anode catalytic microregion of a proton exchange membrane water electrolyzer. A self-consistent electrochemical testing system was constructed within the cell, using an in-situ reversible hydrogen electrode at the cathode. The probe potential-pH response relationship was obtained through electrochemical calibration. Combined with synchronous acquisition technology of electrolysis conditions and electrochemical signals, in-situ, real-time detection of the dynamic pH in the anode catalyst surface microregion under actual energized operation of the proton exchange membrane water electrolyzer was achieved.
2. The method for real-time measurement of the pH surface of the anode catalyst of the membrane electrode under operating conditions in a proton exchange membrane water electrolyzer, as described in claim 1, is characterized in that... Includes the following steps: Step 1: Prepare the iridium / iridium oxide sensing probe for testing:
11. At room temperature, polish the iridium wire with sandpaper; place the polished iridium wire in a mixed solution of ethanol and water for ultrasonic cleaning, and then dry it; 12. Spread a layer of finely ground anhydrous sodium carbonate powder at the bottom of the corundum crucible, then place the iridium wire in the crucible and continue to completely cover the iridium wire with anhydrous sodium carbonate powder.
13. Place the corundum crucible in a muffle furnace and heat it to 800-900℃ at a heating rate of 2-10℃ / min. Hold the temperature for 1-5 hours to generate an iridium oxide sensing functional layer on the surface of the iridium wire in situ. Allow it to cool naturally to room temperature. Rinse the iridium wire alternately with 0.1-0.5 M hydrochloric acid solution and deionized water to completely dissolve and remove the sodium carbonate solid on the surface. Then dry it in an oven at 100-150℃ for 9-15 hours.
14. Soak the dried iridium wire in deionized water for 10-15 days to hydrate it, and you will get an iridium / iridium oxide sensing probe with an iridium oxide coating on the surface.
15. One end of the iridium / iridium oxide sensing probe is wrapped with copper foil as a conductive lead-out end, and the sensing area of the probe is completely wrapped with perforated Nafion film to ensure that the probe can contact the gas and to avoid short circuits when the electrolytic cell is working.
16. Before testing, immerse the prepared iridium / iridium oxide sensing probe in deionized water for 10-15 hours for later use; Step 2, Calibration of probe potential-pH linearity: A three-electrode calibration system was constructed, using an iridium / iridium oxide sensing probe as the working electrode, a calomel electrode as the reference electrode, and a carbon rod as the counter electrode. The open-circuit potential E was measured in a standard buffer solution with a pH range of 2-7. OCP Establish a linear relationship between open circuit potential and pH value; Step 3: Assembly of the proton exchange membrane water electrolyzer and in-situ electrode layout: A proton exchange membrane with a double-sided catalyst layer is used as the core component of the membrane electrode. One side of the membrane is the anode catalyst layer, and the other side is the cathode catalyst layer. The electrolyzer is assembled by stacking layers. On the anode side, platinum-plated titanium felt and anode pad are arranged in sequence from the anode catalyst layer of the membrane to the outside. On the cathode side, carbon paper and cathode pad are arranged in sequence from the cathode catalyst layer of the membrane to the outside. During the assembly and stacking process, the detection electrode is embedded simultaneously. An iridium / iridium oxide sensing probe is placed between the surface of the anode catalyst layer and the titanium felt. A platinum wire wrapped with a perforated Nafion membrane is placed between the cathode catalyst layer and the carbon paper, near the hydrogen outlet, so that the platinum wire is in a hydrogen-saturated environment to serve as an in-situ reversible hydrogen electrode. Step 4: Electrode placement and test system connection: Connect the blue electric test equipment to the electrolytic cell; the working electrode clamp of the Chenhua three-electrode test system holds the copper foil area of the anode iridium / iridium oxide sensing probe, and the reference electrode and counter electrode clamp hold the conductive area of the cathode platinum wire; Step 5: In-situ pH test: Simultaneously activate the Blue Electricity testing system and the Chenhua three-electrode testing system, and acquire the open-circuit potential E measured by the Chenhua three-electrode system in real time. OCP By combining the pre-calibrated potential-pH linear relationship, real-time measurement of the pH on the anode catalyst surface under water electrolysis cell operating conditions can be achieved.
3. The method for real-time measurement of the pH surface of the anode catalyst of the membrane electrode under operating conditions in a proton exchange membrane water electrolyzer, as described in claim 2, is characterized in that... In step 11, the sandpaper has a mesh size of 2000-3000, and the selected iridium wire has a diameter of 0.1-0.2 mm, a length of 10-15 cm, and a purity of 99.99%.
4. The method for real-time measurement of the pH surface of the anode catalyst of the membrane electrode under operating conditions in a proton exchange membrane water electrolyzer, as described in claim 2, is characterized in that... In step 11, the volume ratio of ethanol and water in the mixed solution is 1:1, and the ultrasonic cleaning time is 1-5 hours.
5. The method for real-time measurement of the pH surface of the anode catalyst of the membrane electrode under operating conditions in a proton exchange membrane water electrolyzer, as described in claim 2, is characterized in that... In step 11, the drying temperature is 50-70℃ and the drying time is 5-10 h.
6. The method for real-time measurement of the pH of the anode catalyst surface of a proton exchange membrane water electrolyzer under operating conditions, as described in claim 1, is characterized in that... In step 14, during the 10-15 days of soaking and hydration, the deionized water should be changed every 3 days.
7. The method for real-time measurement of the pH surface of the anode catalyst of a proton exchange membrane water electrolyzer under operating conditions, as described in claim 1, is characterized in that... The iridium / iridium oxide sensing probe and platinum wire are covered by two layers of perforated Nafion film, with a single layer thickness of 6-10 µm.
8. The method for real-time measurement of the pH of the anode catalyst surface of a proton exchange membrane water electrolyzer under operating conditions, as described in claim 1, is characterized in that... In step 3, the thickness of the platinum-plated titanium felt is 400-420 µm, the thickness of the anode PTFE gasket is 400-420 µm, the thickness of the carbon paper is 360-380 µm, and the thickness of the cathode PTFE gasket is 300-320 µm.